STRATEGY OF DIGITAL ETIQUETTE EDUCATION OF ELEMENTARY SCHOOL STUDENTS - Akhwani Akhwani (IKIP Siliwangi, 2019)
The use of digital technology is an inevitable necessity in the era of the Industrial Revolution. Internet access has supported a new digital lifestyle. Digital Native easily accesses the internet and uses digital technology. Navigating the internet is a daily necessity for digital native. They seemed addicted to the internet. Unfortunately, digital natives are not aware of digital traces left behind which can deduce dangerous risks. Progressive education in the era of the industrial revolution is important to develop the concept of character education in accordance with the era. This study aims to find elementary school strategies in forming digital etiquette. The method used in this research is qualitative method. Data collection is done through observation, interviews and documentation. The study involved the principal, and the teacher as research subjects at the Surabaya City Elementary School. The results show that there are three frame approaches developed by schools to embed digital etiquette in elementary schools. Student learning academic performance, School environment and School behavior and Student life outside the school environment. The three frames are used to provide the norms and responsibilities for using digital devices.